Sie sind auf Seite 1von 4

# Section 4.

3 - Rimmer

Laplace Transform L { f ( t )} = ∫ f ( t ) e − st dt = F (s )
0

∞ ∞
{ at
}
L e f (t ) = ∫ e f (t )e dt = ∫ f (t )e −( s − a )t dt = F (s − a )
at − st

a any real 0 0
number
First
Translation laplace of f (t )
Theorem with s − a replacing s

## Section 4.3 - Rimmer

We’ve seen this translation theorem in action already when we derived both

## n ! for integer n > 0

L {t n } =
s n +1 s > 0
n! for integer n > 0
{ }
L t n e at =
(s − a )n+1 s>a

We derived
b
L{sin (bt )} = ,s > 0
s + b2
2

Now, instead of using the definition, we can use the translation theorem to find
b
{
L e at sin (bt ) =} ,s > a
(s − a )2 + b 2

1
Section 4.3 - Rimmer

## Working backwards, we have:

L−1{F (s − a )} = e at f (t )
example 1:
 1  We need to complete the
L−1  2  square in the denominator.
 s − 6 s + 13 
 1  −1  1  −1  2 
L−1  2 = L 
 s − 6 s + 9 + 13 − 9  2  = L  12 2 = 1
e3t sin 2t
 ( s − 3) + 4   ( s − 3) + 4  2

( 1 2 of 6)2
s
example 2: L{cos(bt )} = ,s > 0
s 2 + b2
 s   s   
L−1  2  = L−1  2  = L−1 
s

 s + 4s + 5   s + 4s + 4 + 5 − 4 
2
 (s + 2 ) + 1 
need s + 2 in
the numerator

 s+2−2  −1  s+2 1 
= L−1  2 =L  2
−2 2
−2 t −2 t
 = e cos t − 2e sin t
 ( s + 2 ) + 1   ( s + 2 ) + 1 ( s + 2 ) + 1 

## Section 4.3 - Rimmer

Unit Step Function
on
0, 0 ≤ t < a
U (t − a ) = 
1, t≥a

off

##  0, 0 ≤ t < a  f (t ) OFF, 0 ≤ t < a

f (t )U (t − a ) =  =
 f (t ), t≥a  f (t ) ON, t≥a

 0, 0 ≤ t < π2
sin tU (t − π2 ) =  0 up to π2 and then
sin t , t ≥ π2
picks up sin t at π2

##  0, 0 ≤ t < π2 0 up to π2 and then

sin (t − π2 )U (t − π2 ) = 
sin (t − 2 ),
π
t ≥ π2 shift sin t and start
it at π2

## shift on the t − axis

2
Section 4.3 - Rimmer

Second L { f ( t − a ) U ( t − a )} = e − as L { f ( t )}
Translation
Theorem a any real
number

L{ f (t − a )U (t − a )} = ∫ f (t − a )U (t − a )e − st dt
0
a ∞
= ∫ f ( t − a ) U ( t − a ) e dt + ∫ f ( t − a ) U ( t − a ) e − st dt
− st

0 a
0 for 0 ≤ t < a 1 for t ≥ a

w=t −a t = w+a
= ∫ f ( t − a ) e − st dt
dw = dt t =a⇒w=0
a

∞ ∞
= ∫ f ( w ) e − s( w+ a ) dw = e − as ∫ f ( w ) e − sw dw = e − as L { f ( t )}
0 0   
L { f ( t )}

## Section 4.3 - Rimmer

−π s
e2
L {sin ( t − 2 )U ( t − 2 )} = 2
π π
s +1

 g ( t ) , 0 ≤ t < a
f (t ) =  ⇒ f ( t ) = g ( t ) − g ( t )U ( t − a ) + h ( t )U ( t − a )
 h ( t ) , t≥a

 0, 0≤t <a

f (t ) =  g (t ) , a ≤ t < b ⇒ f ( t ) = g ( t ) U ( t − a ) − U ( t − b ) 
 0, t ≥b

## Alternative form of 2nd Translation Theorem

L { f ( t ) U ( t − a )} = e − as L { f ( t + a )}
a any real
number

3
Section 4.3 - Rimmer

−π s
L {sin ( t ) U ( t − π2 )} = e 2 L {sin ( t + π2 )}
−π s
= e 2 L {cos ( t )}
−π s
e2 s
= 2
s +1